Tradition and Innovation at Catholic Universities: Ideas From the Bernard Lonergan - Teevan, Donna (Catholic Education: A Journal of Inquiry and Practice, 2004)
This article discusses applications of Lonergan’s thinking on tradition and innovation to the world of Catholic education. Even now, at the beginning of the 21st century and 20 years after his death, it is worthwhile to explore his understanding of tradition and innovation, with attention to how it related to the Catholic intellectual culture of his own time, and more importantly, how it might contribute to an understanding of the identity of Catholic educational institutions in today’s period of great transition. In recent years, faculty members and administrators at Catholic universities have been engaged in many discussions about the Catholic intellectual tradition and Catholic higher education. Most of the attention in these conversations has gone to the issue of what it means to be Catholic. The next step is to explore what it means to have a tradition. Thus, this essay examines the usefulness of one leading 20th century Catholic intellectual’s approach to tradition as it relates to Catholic education in general and to Catholic universities in particular.